Salacia juradoi (Celastraceae), a new species from coastal Ecuador - Cornejo, Xavier; Lombardi, Julio A. (Phytotaxa, 2021)
Salacia juradoi (Celastraceae), a new species of tree from the forest remnants of Guayaquil in coastal Ecuador, is here described and illustrated, and the affinities with closely morphologically related taxa is commented. The conservation status of Salacia juradoi is here assessed as Endangered.